Irrigation Volume Based on Pan Evaporation and Their Effects on Water Use Efficiency and Yield of Hydroponically Grown Chilli - Sulistyono, Eko; Juliana, Abe Eiko (Department of Agronomy and Horticulture, IPB University, 2014)
This study was conducted to determine irrigation volume based on pan evaporation and their effects on growth, yield, irrigation water use efficency (IWUE) of chilli grown in sandponic system in the greenhouse. The amount of water used was based on pan evaporation. Irrigation treatments consisted of four coefficients, i.e. 0.5, 1, 1.5, 2 Epan. Plants were watered daily until soil reached field capacity during the first week. Irrigation treatments were applied on the second week until four months later. Total irrigation quantities varied from 9.4 to 37.8 L. plant-1. Chilli fruit yield varied from 3.98 to 90.51 g.plant-1. The highest total fruit yield and IWUE was obtained from 2 Epan treatment. Irrigation treatment had significant effects (P<0.01) on yield and there were positive linear relations between the yield and the amount of irrigation water applied. Irrigation volume significantly increased plant height, number of lateral branches, and number of leaves (P<0.01).Keywords: plant height, lateral branches, fruit